Considerations on the use of ultrasonic pulse velocity, compressive and indirect tensile tests for the quality control of statically compressed earth samples. (16th June 2022) - Rodríguez-Mariscal, José D.; Canivell, Jacinto; Solís, Mario
Rammed earth has become, in recent years, an alternative and more sustainable construction system with respect to techniques that use industrial materials with a greater environmental impact. Although there is currently much research focusing on earthen construction and especially on those techniques based on compacted soil, there are still many physical-mechanical aspects that require further study. Therefore, this article proposes a preliminary study on a specific type of rammed earth using static compaction which, by applying high energy, achieves dry densities similar to the dynamic compaction procedure. In this research, small-size prismatic and cylindrical specimens are tested. The samples are first studied by means of ultrasound pulse velocity (UPV) non-destructive tests. Then, destructive compressive and tensile strength tests are performed. The relationship between UPV along the compaction and perpendicular directions with the mechanical strength and the compaction gradient of the samples is investigated.